Revisiting Indonesian public reactions against Danish cartoons depicting prophet Muhammad - Al Makin (Indonesian Journal of Islam and Muslim Societies, 2015)
This paper revisits the case of cartoon controversy in 2006, particularly focus-ing  on  the way  in which  the  Indonesian  public  reacted  against  the  twelveMuhammad Danish cartoons by the Jylands-Posten published in September 30,2005.  The study remains relevant as the case reflects not only Muslims’ reac-tion  against  the  blasphemy  theologically  but  it  also mirrors  the new  face  ofIndonesian Islam in the reform era which has given birth to a new free public space in which new differing ideologies emerged and were propagated in various media. This study particularly focuses on the selected thirteen op-ed piecesand one interview published by the Indonesian online media in January 2006—three pieces published by Hidayatullah, one posted  in a personal website,  twopublished by Kompas,  two by The  Jakarta Post, one by Gatra,  three by Tempoone  op-ed  and  one  interview  by  JIL  (Islamic Liberal Network). My  analysis  ofthese works reveals two groups with different arguments: radical and conservative  return  to  their  theological  foundation  to  retaliate  the  cartoonists whocommitted blasphemy against  their prophet, whereas  liberals and progressiveIndonesians  rely  on  reasoning  and  draw  cultural  values  in  expressing  theirappraisals of the vilifying  images.Makalah ini berusaha mengkaji kembali kasus kontroversi kartun pada tahun2006,  terutama  berfokus  pada  cara  di mana masyarakat  Indonesia  bereaksiterhadap dua belas kartun Muhammad yang diterbitkan oleh surat kabar Den-mark  Jylands-Posten pada  tanggal 30 September 2005. Studi  ini  tetap relevansebagai  kasus  yang mencerminkan  tidak  hanya  reaksi  umat  Islam  terhadappenghujatan secara teologis tetapi juga mencerminkan wajah baru Islam Indo-nesia di era reformasi yang telah melahirkan ruang publik bebas baru di manaberbagai    ideologi baru muncul dan disebarkan di berbagai media. Penelitianini  terutama fokus pada  tiga belas buah edisi opini dan satu wawancara yangditerbitkan oleh media online Indonesia pada Januari 2006, yang terdiri daritiga potong  yang diterbitkan oleh Hidayatullah,  yang diposting di  sebuah  si-tus  pribadi,  dua  diterbitkan  oleh Kompas,  dua  oleh The  Jakarta  Post,  satuoleh Gatra,  tiga Tempo, satu op-ed dan satu wawancara dengan  JIL  (JaringanIslam Liberal). Analisis  atas  karya-karya  ini mengungkapkan  dua  kelompokdengan argumen yang berbeda: kelompok radikal dan konservatif berpedomanpada  landasan  teologis mereka  untuk membalas  kartunis  yang melakukanpenghujatan terhadap nabi mereka, sedangkan kaum liberal dan progresif In-donesia mengandalkan  penalaran  dan menarik  nilai-nilai  budaya  dalammengekspresikan penilaian mereka atas gambar-gambar tersebut.